Antikvarer og oldforskning på Grundtvigs tid - Adamsen, Christian (Grundtvig-studier, 2006)
Antikvarer og oldforskning på Grundtvigs tid[Antiquarians and the Study of Antiquity during Grundtvig’s Lifetime]By Christian Adamsen While the 17th and 18th centuries were dominated by the so-called antiquarianism, the 19th century saw the dawn of scientific archaeology. The Danish Royal Commission of Antiquities in Copenhagen, established 1807 (much later to become the National Museum), sent out a questionnaire to every clerk in the country in order to collect information about various antiquities. The answers, recently published in full text, reflect not only the local perception of Antiquity all over the country, but also the amount of knowledge available to the commission members in Copenhagen. Central persons in the Danish development are Frederik Munter, Rasmus Nyerup, Christian Jurgensen Thomsen and J. J. A. Worsaae. The relations between Grundtvig and the professional antiquarians were however distant but heartful, still Grundtvig’s lifelong efforts probably constitute the most important contribution to the 20th century status of archaeology as the most widespread Danish hobby.